SYSTEM MODELLING OF BEEF AVAILABILITY IN IKN BUFFER AREAS USING SYSTEM DYNAMICS - Abdallah, Bayu Nur; Kamagi, Kan Grizzel Angelica Fortunius; Wantira, Amanda Dwi (Center for Study and Journal Management FTI UMI, 2024)
There are definitely several of pros and cons when relocating the country's capital from Jakarta to IKN. One of them has to do with the food security. As one of the IKN buffer areas, Balikpapan, has experienced issues with food security, particularly with regard to the supply of beef. The amount of imported beef in 2016-2019 shows a prediction that the amount of imported beef will continue to increase drastically yearly while the amount of local beef tends to decrease. The government of Balikpapan predicts that there will be an increase in the migrant population of up to 20.000 people each year due to the IKN, which can lead to an increase in demand for beef. Factors affecting the availability of beef in Balikpapan are local and imported beef availability, consumption, scarcity, and population demographics. This research was conducted using a system simulation approach with the system dynamic method to describe a complex system regarding the availability of beef in Balikpapan. Based on the scenario that has been developed, an effective policy that can be implemented to maintain the availability of beef in Balikpapan is to increase the cattle feed fraction by 15% and increase the arrival rate of imported beef by 10%. However, there is a need for an intervention policy from the government to increase local beef production, which is predicted to decrease, and minimize the amount of imported beef which dominates in fulfilling the beef consumption needs of the people of Balikpapan.